2001
DOI: 10.1038/sj.ijo.0801584
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein 3 genetic variants in human obesity: the c-55t promoter polymorphism is negatively correlated with body mass index in a UK Caucasian population

Abstract: OBJECTIVE: To investigate whether genetic variation at the UCP3 locus contributes to human obesity. SUBJECTS: Ninety-one obese children (BMI b 4 standard deviations from age related mean) and 419 Caucasian adults from the Isle of Ely Study. DESIGN: Single strand conformation polymorphism (SSCP) analysis was used to scan the coding region of the UCP3 gene in 91 severely obese children. A common polymorphism identi®ed in this gene (c-55t) has been shown to associate with lower UCP3 mRNA expression. Polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 31 publications
7
28
0
Order By: Relevance
“…13,16,17 Some investigators have suggested a functional role of the insertion variant, because it decreases UCP2 mRNA expression, 17 while others failed to show an altered function of the variant. 14 Associations between a À55 c/t polymorphism in the UCP3 promoter and BMI have been reported, 18,19 while other studies find no association. 14,15,[20][21][22] A functional role of the variant has been suggested, because skeletal muscle UCP3 mRNA expression has been reported higher in males, who are hetero-and homozygous for the t-allele compared to males who are homozygous for the c-allele.…”
Section: Introductionmentioning
confidence: 96%
“…13,16,17 Some investigators have suggested a functional role of the insertion variant, because it decreases UCP2 mRNA expression, 17 while others failed to show an altered function of the variant. 14 Associations between a À55 c/t polymorphism in the UCP3 promoter and BMI have been reported, 18,19 while other studies find no association. 14,15,[20][21][22] A functional role of the variant has been suggested, because skeletal muscle UCP3 mRNA expression has been reported higher in males, who are hetero-and homozygous for the t-allele compared to males who are homozygous for the c-allele.…”
Section: Introductionmentioning
confidence: 96%
“…The T allele was associated with higher BMI or waist-to-hip ratio, consistent with decreased function, in French and German Caucasians, South Asian Indian parentoffspring trios, South Asian Indians, and the British Diabetic Association Warren 2 trios collection (29,31,33,48). However, one study showed a lower BMI in TT subjects in a U.K. sample (31), and increased function is also suggested with the association of protection from diabetic neuropathy (22). In these studies association with type 2 diabetes was examined only once, and a relationship was not found.…”
Section: Ucp2-ucp3 and Prospective Diabetes Riskmentioning
confidence: 99%
“…This variant has been associated with changes in fat distribution (waist-to-hip ratio) and BMI (29). In one study the Ϫ55T allele was associated with reduced risk of type 2 diabetes (30), but this was not replicated in other studies (29,31). This variant has also been associated with lower rates of neuropathy in a small study of type 1 diabetes (22).…”
mentioning
confidence: 98%
“…In the first reports of this polymorphism, an influence on body weight was described (24,25), whereas in several following studies, this finding was not confirmed (35)(36)(37)(38). For the C-55T polymorphism in the promoter of the UCP3 gene, several reports described a significant lower BMI for carriers of the TT genotype (29,39). However, other studies did not find an association, suggesting that the influence on BMI might depend on the ethnic background of the study population (26,40).…”
Section: Discussionmentioning
confidence: 58%